2011
DOI: 10.1118/1.3651640
|View full text |Cite
|
Sign up to set email alerts
|

The effect of errors in segmented attenuation maps on PET quantification

Abstract: When using a segmented attenuation map, at least five different tissue types should be considered: cortical bone, spongeous bone, soft tissue, lung, and air. Furthermore, the interpatient variability of lung attenuation coefficients should be taken into account. Limited misclassification from bone to soft tissue and from lung to air is acceptable, as these do not lead to relevant errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 24 publications
(25 reference statements)
8
94
1
1
Order By: Relevance
“…A study conducted by our group (9) showed an underestimation greater than 10% for 58% of osseous regions when a segmentation-based method that ignored bone was used. Keereman et al reported an underestimation of 10%-20% in spine and femur lesions if cortical bone was ignored, versus 10%-15% if soft bone was ignored (32).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by our group (9) showed an underestimation greater than 10% for 58% of osseous regions when a segmentation-based method that ignored bone was used. Keereman et al reported an underestimation of 10%-20% in spine and femur lesions if cortical bone was ignored, versus 10%-15% if soft bone was ignored (32).…”
Section: Discussionmentioning
confidence: 99%
“…In 3-or 4-class MRAC methods, bones are replaced by soft tissue and the inter-or intrapatient heterogeneity of attenuation coefficients in different tissue classes is ignored, which leads to quantification errors in the estimation of standardized uptake value (SUV) ranging between 4% and 25% in different organs (9)(10)(11)(12)(13). Using the PET/CT datasets of 35 patients, Martinez-Möller et al reported an average SUV error of 8.0% 6 3.3% in 21 bone lesions and less than 5% in all other lesions (5).…”
mentioning
confidence: 99%
“…In brain PET, ignoring bone has been suggested to cause quantification bias (29) . In whole‐body PET/MR imaging, however, neglecting bone in segmented attenuation images has been suggested to cause large errors only in regions that are inside or near bones 30 , 31 , 32 . In one example demonstrated by Samarin et al, (32) classifying bone as soft tissue resulted in less than 6% difference for PET voxels in the heart region.…”
Section: Discussionmentioning
confidence: 99%